Earth Observation for Rangeland Intelligence: Mapping, Monitoring, Managing - Paliwal, Ambica (International Livestock Research Institute, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025